Pseudogout Overlapping with Pre-Existing Joint Pathologies: A Case Series - Johanda Damanik; Rizki Fauzi Suskhan; Rendy Asmaradhana Sahara; Rudy Hidayat; Suryo Anggoro Kusumo Wibowo; Anna Ariane; Faisal Parlindungan; Abirianty Priandani Araminta (Indonesian Journal of Rheumatology, 2026)
Pseudogout, or calcium pyrophosphate deposition disease (CPPD), is a crystal-induced arthritis frequently mistaken for gout or septic arthritis, particularly in elderly patients or those with inflammatory disorders. We present two cases highlighting the diagnostic value of synovial fluid analysis and musculoskeletal ultrasonography (MSUS). A 34-year-old man diagnosed with ankylosing spondylitis presented with acute right knee pain after running; synovial fluid revealed rhomboid-shaped crystals with high leukocyte count, confirming pseudogout, while MSUS showed intra-cartilaginous crystal deposits. An 87-year-old man presented with mild left knee pain and swelling; synovial fluid again demonstrated rhomboid-shaped crystals, and MSUS confirmed intra-cartilaginous crystal deposition, consistent with pseudogout coexisting with osteoarthritis. These cases highlight the diagnostic challenges of acute monoarthritis in chronic inflammatory disease and advanced age, where inflammatory markers may mislead. Synovial fluid crystal analysis remains crucial, while MSUS offers a non-invasive alternative when aspiration poses challenges, ensuring accurate diagnosis and appropriate anti-inflammatory therapy.